1982
DOI: 10.1111/j.1151-2916.1982.tb10361.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of SiO2-Al2O3 Glasses

Abstract: The structure of SiOz-Alz03 glasses with up to 60 wt % AIzO3 was investigated using the radial distribution function together with the correlation method based on X-ray scattering intensity data. Radial distribution curves are interpreted on the basis of glass-in-glass separation with the constituents of SiOz-rich and AIzO3-rich glasses. The structure of the AlzOa-rich glass has a short-range ordering similar to the crystal structure of mullite. The calculated S i ( S ) curve of this model gives good agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 10 publications
9
50
2
Order By: Relevance
“…As the Al-O bond length in the tetrahedral site is 0.13 Å longer than the Si-O bond length in the tetrahedral site (Shannon 1976), the average first nearestneighbor T-O (T = Si, Al) lengths in SiO 2 -Al 2 O 3 glasses are longer than the Si-O length. These lengths for SA1 and SA2 were between that of SiO 2 glass (1.59 Å; Meade et al 1992) and those of SiO 2 + 25.0 mol% Al 2 O 3 glass Morikawa et al 1982), showing that our results were in agreement with previous studies about T-O lengths at ambient conditions. Brillouin peaks from the transverse acoustic modes of both SA1 and SA2 were observed over the entire pressure range up to 169.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As the Al-O bond length in the tetrahedral site is 0.13 Å longer than the Si-O bond length in the tetrahedral site (Shannon 1976), the average first nearestneighbor T-O (T = Si, Al) lengths in SiO 2 -Al 2 O 3 glasses are longer than the Si-O length. These lengths for SA1 and SA2 were between that of SiO 2 glass (1.59 Å; Meade et al 1992) and those of SiO 2 + 25.0 mol% Al 2 O 3 glass Morikawa et al 1982), showing that our results were in agreement with previous studies about T-O lengths at ambient conditions. Brillouin peaks from the transverse acoustic modes of both SA1 and SA2 were observed over the entire pressure range up to 169.…”
Section: Resultssupporting
confidence: 93%
“…The SiO 2 -Al 2 O 3 system is the simplest from among the aluminous silicate systems. A number of previous studies have reported structural features at ambient pressure, as inferred by Raman scattering (Kato 1976;McMillan and Piriou 1982), infrared absorption (Poe et al 1992a;Okuno et al 2005), X-ray diffraction (Morikawa et al 1982;Okuno et al 2005), nuclear magnetic resonance (NMR) spectroscopic techniques (Risbud et al 1987;Sato et al 1991;Poe et al 1992a, b;Sen and Youngman 2004;Weber et al 2008), and by molecular dynamics (MD) computer simulations (Poe et al 1992a, b;Linh and Hoang 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Morikawa et al 1982, Brown et al 1995and references therein, Stebbins 1995, McMillan & Wolf 1995. Morikawa et al (1982) carried out an X-ray-scattering study of a number of compositions along the join Al 2 O 3 -SiO 2 . They noted that these glasses are phase-separated into a SiO 2 -rich and an Al 2 O 3 -rich phase.…”
Section: Aluminum (Al 3+ )mentioning
confidence: 99%
“…Thus, unlike SiO 2 , Al 3+ ions do not form a network of AlO 4 tetrahedra that are connected with each other via the O atoms at the corners. Instead, different experimental techniques such as nuclear magnetic resonance (NMR) [Lee and Stebbins, 2000;Schmücker et al, 1999;Sen and Youngman, 2004;Stebbins et al, 2005;Stebbins and Xu, 1997; Xue and Kanzaki, 1999] as well as IR and Raman spectroscopy and X-ray scattering [Morikawa et al, 1982;Okuno et al, 2005] found evidence for structural units such as three-fold coordinated oxygen atoms and five-and six-fold coordinated aluminium atoms that are not found in pure silica, unless one considers amorphous silica at very high temperatures, say above 4000 K (see Horbach and Kob, 1999).…”
Section: Introductionmentioning
confidence: 99%